Neurites containing the neurofilament-triplet proteins are selectively vulnerable to cytoskeletal pathology in Alzheimer’s disease and transgenic mouse models - Mitew, Stanislaw; Kirkcaldie, Matthew T.; Dickson, Tracey C.; Vickers, James C. (Frontiers in Neuroanatomy, 2013)
Amyloid-β plaque accumulation in Alzheimer’s disease (AD) is associated with dystrophic neurite formation and synapse loss in principal neurons, but interneuron pathology is less clearly characterised. We compared the responses of neuronal processes immunoreactive for either neurofilament triplet (NF+) or calretinin (CR+) to fibrillar amyloid (Aβ) plaques in human end-stage and preclinical AD, as well as in APP/PS1 and Tg2576 transgenic mouse AD models. Neurites traversing the Aβ plaque core, edge or periphery, defined as 50, 100 and 150% of the plaque diameter respectively, in human AD and transgenic mouse tissue were compared to age-matched human and wild-type mouse controls. The proportion of NF+ neurites exhibiting dystrophic morphology (DNs) was significantly larger than the proportion of dystrophic CR+ neurites in both human AD and transgenic mice (p < 0.01). Additionally, the number of NF+, but not CR+, DNs, correlated with Aβ plaque size. We conclude that CR+ interneurons appear to be more resistant than NF+ neurons to AD-mediated cytoskeletal pathology.